12 things to know about the Iron Age - Marquardt, Meg (Marquardt, Meg. Prehistoric., 2020)
Describes twelve aspects of the Iron Age, including the origins of working with iron and explains how this innovation led to the development of large empires, complex architecture, and the development of money. Includes illustrations, a timeline, a glossary, and resources for further information.